The Urgency of Adopting the Norma Convention on Cybercrime in Amendment to Law No 11 of 2008 Concerning Electronic Information. Seviadian - Permadi, Sevia Dian Rianita; Risna, Muh; Guna Nugraha, Lalu (Department of Law, Faculty of Law, University of Mataram, 2023)
The purpose of this study is to analyze the urgency of adopting the Convention on Cybercrime in changing Law no. 11 of 2008 concerning Information and Electronic Transactions focuses on forms of legal protection against cybercrime before and after the passage of the Electronic Information and Transaction Law (UU ITE) and the urgency for ratification of The Convention on Cybercrime in Indonesia. In this study using a type of normative research. Based on the results of this study it is known that the Urgency of Adopting the Convention on Cybercrime in Amending Law No. 11 of 2008 concerning Information and Electronic Transactions, especially the form of legal protection against cybercrime before and after the passage of the Electronic Information and Transaction Law and the urgency of ratifying The Convention on Cybercrime in Indonesia, so that in cases of cybercrime or Cybercrime in Indonesia. Based on the provisions of the Convention on Cybercrime, cybercrime offenses are generally regulated in the convention. However, every country is given the opportunity to develop and adapt to the needs of that country without putting aside the interests of the international community. Therefore, the law used is neutral, and the form of punishment regulated in the Convention on Cybercrime is a minimum standard provision. If adopted,The urgency of adopting the norms of the Convention on Cybercrime in changing Law no. 11 of 2008 concerning Information and Electronic Transactions is to complement the weaknesses of the Act regarding international cooperation.This of course can make it easier for the Indonesian government to tackle cyber crime through international cooperation mechanisms.